IMPLEMENTASI KEBIJAKAN PROGRAM PEMBERDAYAAN MASYARAKAT DALAM MENDUKUNG KEGIATAN PEMBANGUNAN DI DISTRIK SUGAPA KABUPATEN INTAN JAYA - Zulfikar Bintang; Nur Aedah (JURNAL KEBIJAKAN PUBLIK, 2022)
The issue of village development has become a priority for realizing development from the lowest level of government. Particularly in poverty alleviation priorities of rural communities. One of the activities aimed at building and prospering the village community is contained in Law No. 6 of 2014 on the Village, which is the activities of BUMDes. This research is conducted to know the implementation of the policy of BUMDes in Sugapa District Intan Jaya Regency. The correct management and implementation and in accordance with the policies made are expected to realize the ideals of BUMDes establishment. This research uses qualitative descriptive writing method. The data source used is primary data and secondary data. The study used the data obtained through interview, bservation and documentation. The theoretical basis used is the theory of policy implementation of Van Meter and Van Horn explains that policy implementation is an action to transform policy into action that is operational by government or private that directed to reach the purpose which have been determined. There are 6 variables of policy implementation according to Van Meter and Van Horn are Policy Objectives, Resources, Inter-Organizational Relations, Characteristics of implementing agencies/ organizations, Political, social and economic environment, Disposition/ response or attitude of the implementers. The process of policy Implementation BUMDes Sejahtera Sugapa District can run smoothly. The achievement of BUMDes welfare mission-mission can be realized. The resources of the marine can be well explored. The relationship between supervisors, administrators and members of BUMDes is conducive. The political, social and economic sectors can thrive. It is based on the level of understanding of the very high actors of economic development and poverty alleviation in Sugapa District. Neither the Village Government nor the managers of BUMDes Sejahtera.